Prevalence of Different Types of Keratosis in Patients in a University Setting - P. Keshaav Krishnaa1 , Manjari Chaudhary2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The most commonly occurring type of keratosis would be tobacco pouch keratosis or smokeless tobaccoassociated keratosis, frictional keratosis, a chronic frictional keratosis on the buccal mucosa can lead tosomething called morscicatio buccarum. Although clinical features are very important and should be oneof the important factors in diagnosis, epidemiology should also be considered while arriving at a concretediagnosis. The aim of the present study was to retrospectively analyze the prevalence of different clinicalvariants of Keratosis in patients visiting Saveetha Dental College. Retrospective data of 195 patients wasobtained and segregated. Inclusion criteria included that they should have visited the University betweenJune 2019 and April 2020. Once the data was obtained and verified, it was statistically analyzed using SPSSby IBM version 20. Most common clinical variant was Tobacco pouch Keratosis (64.6%) followed byFrictional Keratosis (28.7%). Mean age of the patients was 37.40 + or -10.98 years. Tobacco pouch keratosisoccurring most commonly in lower arch (67.46%) whereas the Frictional keratosis most commonly inrelation to both arches (42.85%). All common in 21-30 years age group. Statistically significant correlationbetween the site of lesion and variant (p = 0.000) and between gender and variant (p=0.00 ) Increased HabitPrevalence as the number of Tobacco pouch Keratosis cases are greater. Further multicentered studies andawareness programs to help the society and prevent these lesions.